2, 2-Bis(hydroxymethyl) propionic acid based cyclic carbonate monomers and their (co)polymers as advanced materials for biomedical applications. (August 2021) - Ansari, Imran; Singh, Prabhjeet; Mittal, Anupama; Mahato, Ram I.; Chitkara, Deepak
Abstract: Designing grafted biodegradable polymers with tailored multi-functional properties is one of the most researched fields with extensive biomedical applications. Among many biodegradable polymers, polycarbonates have gained much attention due to their ease of synthesis, high drug loading, and excellent biocompatibility profiles. Among various monomers, 2, 2-bis(hydroxymethyl) propionic acid ( bis-MPA ) derived cyclic carbonate monomers have been extensively explored in terms of their synthesis as well as their polymerization. Since the late 90s, significant advancements have been made in the design of bis-MPA derived cyclic carbonate monomers as well as in their reaction schemes. Currently, bis-MPA derived polycarbonates have taken a form of an entire platform with a multitude of applications, the latest being in the field of nanotechnology, targeted drug, and nucleic acid delivery. The present review outlines an up to date developments that have taken place in the last two decades in the design, synthesis, and biomedical applications of bis-MPA derived cyclic carbonates and their (co)polymers. Graphical abstract: Image 1